Polypharmacy at admission prolongs length of hospitalization in gastrointestinal surgery patients. Issue 11 (22nd September 2020) - Abe, Natsuki; Kakamu, Takeyasu; Kumagai, Tomohiro; Hidaka, Tomoo; Masuishi, Yusuke; Endo, Shota; Kasuga, Hideaki; Fukushima, Tetsuhito
Abstract : Aim: Polypharmacy in elderly people is a social issue and has been reported to cause not only drug adverse events, but also falls, dysfunction and cognitive decline. Those events may trigger prolonged length of hospitalization. Therefore, the aim of this study was to investigate whether polypharmacy has a prolonging effect on hospitalization. Methods: The study subjects were 584 patients in a university hospital in Japan who had been admitted for hepatectomy, pancreaticoduodenectomy, gastrectomy or colectomy, and to whom clinical pathways had been applied. In this study, polypharmacy was defined as taking five or more regular oral medications, and prolonged hospitalization was defined as hospitalization longer than that determined by the clinical pathway. Multiple logistic regression analysis was performed to investigate whether polypharmacy affects the length of hospitalization. Results: The subjects were 348 males and 236 females, mean ± SD age of 65.8 ± 12.9 years. Among all subjects, 228 (39.0%) were receiving polypharmacy at admission, and the number of patients with prolonged hospitalization was 262 (44.9%). Multiple logistic regression analysis revealed that the following variables were significantly associated with prolonged hospitalization; polypharmacy (odds ratio = 1.532; 95% confidence interval = 1.010–2.327), age 50–59; 2.971 (1.216–7.7758), age 60–69; 2.405 (1.059–5.909), organ pancreas; 0.298 (0.122–0.708), operation time ≥386 min; 2.050 (1.233–3.432), intraoperative bleeding volume ≥401 mL; 2.440 (1.489–4.038), postoperative delirium; 2.395 (1.240–4.734), postoperative infection; 10.715 (4.270–33.059). Conclusion: The current study revealed that polypharmacy at admission was an independent factor for prolonged hospitalization. In future, measures against polypharmacy are required, collaborating with outpatient clinics, family doctors and dispensing pharmacies. Geriatr Gerontol Int 2020; 20: 1085–1090. .